A Randomized Multicenter Study Comparing a Tacrolimus-Based Protocol with and without Steroids in HCV-Positive Liver Allograft Recipients. (28th May 2012) - Neumann, Ulf; Samuel, Didier; Trunečka, Pavel; Gugenheim, Jean; Gerunda, Giorgio Enrico; Friman, Styrbjörn
Abstract : Allograft reinfection with hepatitis C virus (HCV) occurs universally in liver transplant recipients. Corticosteroids can contribute to HCV recurrence. This randomized study evaluated HCV recurrence in HCV-positive liver allograft recipients using steroid-free immunosuppression. All patients received tacrolimus (TAC) at an initial dose of 0.10–0.15 mg/kg. The steroid-free arm (TAC/daclizumab (TAC/DAC, n = 67 )) received daclizumab induction, and the steroid arm (TAC/steroid (TAC/STR, n = 68 )) received a steroid bolus (≤ 500mg) followed by 15–20 mg/day with discontinuation after month 3. Median HCV viral load at month 12, the primary endpoint, was similar at 5.46 (0.95–6.54) IU/mL with TAC/DAC and 5.91 (0.95–6.89) IU/mL with TAC/STR. Small numerical differences in the estimated rate of freedom from HCV recurrence (19.1 versus 13.8%) and freedom from biopsy proven rejection (78.4 versus 66.1%) were observed between TAC/DAC and TAC/STR. Patient survival estimates were significantly lower with TAC/DAC than with TAC/STR (83.1 versus 95.5%; 95% CI, −0.227 to −0.019%), and graft survival was numerically lower (80.1 versus 91.1%, P = NS ). Completion rates (45 versus 82%) indicated poorer tolerability with TAC/DAC than with TAC/STR. Steroid-free immunosuppression had no real impact on HCV viral load. HCV recurrence was higher with TAC/STR. Results are inconclusive due to the unexpected lower completion rates in the TAC/DAC arm.